Kopontren Optimization to Promote Digital Economic Transformation in the Dzikrul Ghofilin Al Hasyimiyyah Islamic Boarding School and Surrounding Communities - Muhammad Khotib Khusaen Fikri; Nurul Wulandari Putri; Muhammad Afani Adam (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: The Dzikrul Ghofilin Al Hasyimiyyah Islamic Boarding School Cooperative (Kopontren) has strategic potential as a driving force for digital economic transformation, but still faces challenges in optimizing the use of technology for the economic empowerment of students and the surrounding community. Objective: This study aims to analyze Kopontren's optimization strategies in promoting digital economic transformation, identify the potential and challenges of implementation, and formulate a sustainable transformation roadmap to improve the economic welfare of the pesantren community and its surroundings. Method: The study employs a descriptive qualitative approach using a case study method. Data was collected through direct observation, in-depth interviews with key stakeholders, document analysis, and SWOT analysis. Data analysis utilized triangulation techniques to ensure the validity and reliability of the findings. Result: The study identified three key strategies for optimizing Kopontren: (1) digitizing internal management systems through the implementation of integrated information systems and mobile applications; (2) developing e-commerce platforms and integrating them with marketplaces to expand market reach; (3) implementing sharia fintech and community digital literacy empowerment programs. Implication: This transformation model can be replicated in other Islamic boarding schools as a best practice for digital-based economic empowerment of the Muslim community while maintaining Islamic values. Policy implications highlight the need for government support in the form of conducive regulations, human resource training programs, and access to capital to accelerate the adoption of digital technology within Islamic boarding schools.